Application of nano-titanum dioxide coating on fresh Highbush blueberries shelf life stored under ambient temperature. (February 2021) - Rokayya, Sami; Jia, Fuguo; Li, Yang; Nie, Xin; Xu, Jingwen; Han, Rui; Yu, Huiying; Amanullah, Sikandar; Almatrafi, Manal Mused; Helal, Mahmoud
Abstract: Blueberries are non-climacteric fruits which have a limited shelf life due to the activities of rapid decay and softening. Coatings are eco-friendly by nature which helps in prolonging fruits and vegetable storage life. This research was carried out to determine the effects of nano-coatings on blueberries' life extension with 50–65% humidity for 8 days at ambient temperature. Different formulated coatings of chitosan (BC), chitosan/nano-titanium dioxide (BC-NT), and chitosan/nano-titanium dioxide (tween-thymol) (BC-NT-TT) were developed and used to check their effectiveness against some physical, mechanical and biochemical properties in addition to microbiological analysis and sensorial evaluations. The use of BC-NT-TT coating treatment was proved to prolong storage life as well as several quality parameters like weight loss (1.97%), decay rate (5.56%), shrinking rate (32.69%), ascorbic acid content (7.78 mg/100 g), appearance, texture, and antioxidant enzymes. Moreover, BC-NT-TT coating lessened the mesophilic aerobic bacteria, mould, and yeasts counts. BC-NT coatings enhanced pH (3.07), soluble solids content (9.64 °Brix), ripening index (21.42), and as well as anthocyanins (65.76 mg/100 g). BC coating significantly described the highest titratable acidity (0.41%) value. An over-all sensorial evaluation has remained acceptable and the final results indicated that BC-NT-TT should be used for preservation instead of other expensive and artificial chemicals. Graphical abstract: Image 1 Highlights: A combination coating of chitosan and nano-titanum dioxide with some microbial agents were prepared. The effect of coating on quality changes was measured under ambient temperature. Chitosan/nano-titanium dioxide (tween-thymol) treatment was the best for Highbush Blueberries shelf life.